Lost futures? Educated youth precarity and protests in the Oromia region, Ethiopia. Issue 6 (1st November 2020) - Abebe, Tatek
ABSTRACT: Drawing on ethnographic fieldwork, this article explores the connections between young people's livelihoods, education and visions of the future in Ethiopia. It engages with educated youth's narratives of precarity, dispossession, and 'intimate exclusions, ' discussing how development has impacted rural livelihoods. Educated youth protests in the Oromia region reveal how shortages of farmland and education play crucial roles in the conflict about sovereignty and development. Qeerroo (Oromo youth) are particularly active in the protests because they are excluded from a rural future through land grabbing and population growth as well as from a modernist development future that unequally distributes the fruits of economic growth. By politicizing educated unemployment and landlessness and connecting them to neoliberal capitalism, this article analyses the intentions of the Ethiopian state to 'save' its youth through economic development while youths claim to 'lose' their futures to generate grassroots politics. The article also draws analytical attention to why there is a need to rethink concepts like development, waithood, and rural futures.